Strategi Mahasiswa Meningkatkan Motivasi Belajar Berbicara Bahasa Arab pada Pembelajaran Maharah Al-Kalam: Studi Kasus di Sekolah Tinggi Ilmu Tarbiyah Hidayatunnajah Bekasi - Nur’afifah, Asiah; Mulhendra, Mulhendra; Muslim, Muslim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to examine the strategies of students of the Arabic language education study program in increasing self-motivation in learning Arabic speaking skills, how students perceive self-motivation, and the obstacles experienced in increasing self-motivation in learning Maharah Al-Kalam. This research uses qualitative research case study method. The research location is one of the tarbiyah colleges in Bekasi with five participants in semester 4 students. Participants were taken by simple random sampling technique. Data sources were obtained through questionnaires and interviews via whatsapp messages. After the data is collected, it is then analyzed by reducing the data, presenting the data and finally making conclusions. As a result, the author found intrinsic motivation in students related to the ideals / aspirations / desires that exist in themselves, their ability to follow the learning process and their interest in the courses they followed. While their extrinsic motivation is influenced by language elements in related courses, friends around them and teachers who teach. From all the findings obtained, the author found several interesting things to be tried by all students in increasing motivation to learn Arabic, especially Maharah Al-Kalam courses, namely by often watching Arabic videos, and talking to friends and teachers using Arabic even though only a word they were able to. Coupled with teachers who always provide motivation before or after lectures so that student motivation increases. By maximizing the existing intrinsic and extrinsic motivation and trying to understand and solve the obstacles experienced during learning yourself, it turns out to be quite effective in increasing self-motivation and the smooth learning process.